Accompaniment Application of the Talaqqi Method for Increase Ability Reading the Qur’an, Ladies of the Assembly Ta'lim Pandai Sikek - Sri Wahyuni; Fatimah Harfitriani; Annisa Aulia; Annisa Harianja; Auliana Muslimah; Humaidah Farisa Aina Nuha Lubis; Khosyanti Salsabila Hasibuan (As-sunnah: Jurnal Pengabdian Masyarakat, 2024)
The "Majelis Ta'lim Pandai Sikek" is a group of community mothers who are active in Quran reading activities in mosques. Many issues arise in Quran reading, such as a lack of understanding of Quranic reading, where individuals merely read without grasping the Makharij al Huruf (articulation points of letters) or understanding the meanings of Quranic verses. To address this, specific methods are needed to enhance the Quran reading abilities of the mothers in the Majelis Ta'lim Pandai Sikek community. The Talaqqi method has been proven effective in improving Quranic recitation skills. The goal of this activity is to provide guidance to the Pandai Sikek community in improving their Quranic recitation using the Talaqqi method. This activity is conducted by lecturers from the University of Muhammadiyah West Sumatra and students from the Community Service Program (KKNT) of the As-Sunnah Islamic High School in Deli Serdang. The results indicate an improvement in the Quranic recitation abilities of the Pandai Sikek community. Initially, twenty mothers faced issues with Quranic recitation related to articulation points, but by the end of the program, seventeen mothers could recite fluently according to the correct articulation points. Four mothers who initially struggled with Quranic recitation could read fluently by the end of the program. Challenges encountered during the implementation of the activity include some mothers leaving the sessions midway to attend to household activities.